Transformation of funding sources during the COVID-19 pandemic - Yu Rui Zhang; A. Z. Nurmagambetova; M. H. Abenova; N. Berdimurat; A. S. Jondelbayeva (Экономика: стратегия и практика, 2021)
The rapid spread of the COVID-19 pandemic in the world in the second half of 2020 caused a decline in the country’s external economy. The demand crisis in most sectors of the world economy triggered a global collapse of stock market indices and a sharp drop in energy prices.The period of the pandemic also affected the financial behavior of investors. Recent research on the impact of the COVID-19 pandemic confirms the relationship between financial attitudes and behavior, which contains more questions than statements. In this article, the authors studied the behavior of investors during the crisis (COVID-19). The article analyzes the method of an artificial neural network (ANN). The study will help academics and policymakers understand investor behavior and their impact on financial reporting performance.